Blood-based biomarkers of cancer-related cognitive impairment in non-central nervous system cancer: protocol for a scoping review. Issue 1 (27th January 2018) - Mayo, Samantha J; Kuruvilla, John; Laister, Rob C; Ayala, Ana Patricia; Alm, Mark; Byker, Will; Kelly, Debra Lynch; Saligan, Leorey
Abstract : Introduction: Cancer-related cognitive impairment (CRCI) can have detrimental effects on quality of life, even among patients with non-central nervous system (CNS) cancers. Several studies have been conducted to explore different markers associated with CRCI to understand its pathobiology. It is proposed that the underlying mechanisms of CRCI are related to a cascade of physiological adaptive events in response to cancer and/or treatment. Hence, peripheral blood would be a logical source to observe and identify these physiological events. This paper outlines the protocol for a scoping review being conducted to summarise the extant literature regarding blood-based biomarkers of CRCI among patients with non-CNS cancer. Methods/analysis: Methods will be informed by the updated guidelines of Arksey and O'Malley. The systematic search for literature will include electronic databases, handsearching of key journals and reference lists, forward citation tracking and consultation with content experts. Study selection will be confirmed by duplicate review and calculation of inter-rater reliability. Data to be charted will include study design, sample size, cancer and treatment characteristics, demographic characteristics, cognitive variable/s and biomarkers assessed, associations between cognitive functioning and biomarkers (including statistics used), and rigour in biomarker sample collection and processing. Results will be presented through: (1) a descriptive numerical summary of studies, including a flow diagram based on the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement, (2) a list of blood-based biomarkers associated with CRCI and (3) a narrative overview developed through collaboration among the research team and consultation with content experts. Dissemination: The findings of this review will highlight current directions and gaps in the current body of evidence that may lead to improved rigour in future CRCI investigations. The dissemination of this work will be facilitated through the involvement of clinicians and researchers on the research team, an external consultation process and the presentation of the results through scholarly publication and presentation.